Numerical analysis of fuzzy logic temperature and humidity control system in pharmaceutical warehouse using MATLAB fuzzy toolbox - Nurainaa, Elias; Nafrizuan, Mat Yahya; Sing, Er Hong (Springer, 2018)
This paper describes the simulation for performance evaluation of fuzzy logic controller in pharmaceutical warehouse’s temperature and humidity control system by using MATLAB Fuzzy Logic Toolbox and MATLAB Simulink. MATLAB fuzzy toolbox is used where a fuzzy logic controller is designed to simulate the control system based on control input such as user desired temperature, user desired humidity and deviation from desired parameters. The output control will be the cool fan speed, operation speed of ventilation fan (humidifier) and exhaust fan (dehumidifier). The result will be described in terms of the speed of output actuators changing with the difference in input temperature and humidity. The results of the Simulink model with optimized efficient and good performance are presented. The main aim is to achieve the output actuators with good performance, stable and smooth as the desired set point temperature and humidity and also develop fuzzy inference control system to simulate and monitor the desired temperature and ventilation system in pharmaceutical warehouse area.